Digitized technology and evolving selfie obsession among University of Port Harcourt students: A gendered culture? - God’spresence, Emily Oghale; God’spresence, Azuka F.N. (Journal of Gender and Power, 2021)
Digitization is a prime globalized ideology in the 21st century high tech revolution. It essentially deals with automation of manual process to make room for easy documentation and sustainable data regime. Africa is an emerging digital domain with many of its young generation becoming keen lovers of Information Technology (IT), and many of the youth population fast becoming internet devotees, social and new media addicts. One of the trending fantasies, among the numerous exploitations and innovations of the new technology is selfie. Selfie is simply a selfphotograph of a person’s portrait by himself. This is possible by the use of smartphone or digital camera held out at arm’s length by the person taking the snapshot. Presently, there is craze for digital identity among African youths. It is against this background that undergraduate students at the University of Port Harcourt were sampled purposively for deployment in this study. This study utilizes questionnaire and Focus Group Discussion (FGD) as instruments for data gathering in order to determine whether the use of selfies is more common to the male or female members of the African digital society. Finally, the study is guided by Uses and Gratification theory and Symbolic Interactionism Theory.